Alkane degradation mechanism of Mixta calida HXX308 isolated from sediment of the Mariana Trench - Yang, Yizi; He, Xinxin; Zhang, Yulin; Zhang, Xiao-Hua (Frontiers in Microbiology, 2025)
The Challenger Deep of the Mariana Trench, which is the deepest site in the ocean, contains rich deposits of n-alkanes in its sediments. However, the alkane metabolic processes of the bacteria in this extreme environment were not well understood. In this study, we isolated a strain Mixta calida HXX308 (Proteobacteria) from sediment samples of the Challenger Deep (10,816 meters below sea level). HXX308 grows under pressures ranging from 0 to 40 MPa, with optimal growth at lower pressures. Additionally, it degrades approximately 20% of eicosane at both atmospheric pressure (0.1 MPa) and 20 MPa. Metabolic profiling indicated that HXX308 possesses a complete aerobic alkane metabolism pathway, along with nitrate reduction and sulfate reduction pathways, which support its adaptation to the trench’s anoxic environment. Comparative genomic studies showed that most strains in the genus Mixta contain the alkane-degrading gene LadB. Characterization of the LadB gene in HXX308 confirmed its role in the degradation of medium-to long-chain alkanes (C18-36). HXX308 is the first Mixta strain isolated from marine environment. Although this strain originated from the trench, its hydrocarbon metabolic characteristics are similar to those of cultures of terrestrial origin, suggesting that the alkanes in these sediments are likely from the terrestrial environment. Our study enhances the understanding of alkane-degrading in the phylum Proteobacteria and provides insights into the environmental adaptation of M. calida HXX308 in the Mariana Trench.